AB0966 Pigmented Villonodular Synovitis: Not Only Synovectomy. (9th June 2015) - Lattanzi, B.; Lanni, S.; Luniew, E.; Giangiacomi, M.; Ravelli, A.; Jorini, M.
Abstract : Background: Pigmented Villonodular synovitis (PVNS) is a rare disease in children. The treatment of choice is the synovectomy, which nevertheless often results in joint function impairement, especially in pediatric subjects in which more frequently it may affect growth plates with residual damage. To date, the first-line treatment of PVNS is the partial or total synovectomy, that may be performed during arthroscopic procedure or with arthrotomy, respectively, with high incidence of recurrence in case of arthroscopy. The association of local post-operative radiation therapy has been reported to be effective in preventing recurrence, thus avoiding the need for subsequent surgical procedures. However, the use of radiation therapy in children is currently controversial due to limited case reports Methods: SG, an 11-year-old, male, came under our observation for swelling, pain and functional impairment of the left knee. Medical history unveiled that six months before the boy had experienced a similar episode, with evidence of intra-articular effusion and thickening of the synovium at the ultrasound assessment. The clinical picture had gradually subsided till resolution in about a month, apparently benefitting from rest and local application of ice. After three months of well-being, swelling with minimal functional limitation and pain after exertion recurred and the boy was, thus, sent for rheumatological consult. At the physical examination, the left knee was found to be swollen with minimal functional limitation. The routine blood testing and immuno-assays were not significant. In particular ANA were negative. The ultrasound showed intraarticular corpusculated effusion. Arthrocentesis was performed and resulted in 50 ml of frankly bloody synovial fluid. MRI (T1 sequences S, MultiEco, GE T2 and STIR) was suggestive of diffuse PVNS. The exploratory arthroscopy with synovial biopsy confirmed the radiological diagnosis. Immunohistochemistry showed the presence of an inflammatory infiltrate with a CD3+CD8+ prevailing component, associated with a CD68+ monocytic subset and only a minimal CD19 + plasma cell infiltrate. By adopting a more conservative approach, the patient underwent 2 intra-articular infiltration of triamcinolone hexacetonide (40 mg/dose) at a distance of 3 months, and a significant clinical improvement of the swelling and functional limitation was obtained. MRI control performed after 7 months showed significant reduction of intra-articular effusion and stationary panelSynovial hyperplasia. Conclusions: The case herein described showed the efficacy, although partial, of intra-articular infiltration as bridging treatment in children with PVNS. This conservative therapeutical approach may be a valuable alternative that can allow to delay the synovectomy until the closure of the growth plates had been occurred, thus limiting the risk of secondary outcomes related to residual damage due to surgical procedure in children. Disclosure of Interest: None declared